The impact of using automation technology in high technology manufacturing company - Matius, Juanis. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The application of automation technology plays an important role for improvement of manufacturing technology in our countries. The convergence of advanced technology in electronic fields, electrical fields, mechanical fields and control fields made this system as a smart system which direct or indirectly effects in high technology manufacturing. A brief explanation about the impact of using automation technology in high technology manufacturing based on theory and practical approach done in this thesis. The main objective of this study is to find the impact of using automation technology in high technology manufacturing in Sarawak, Malaysia. The general objective of this study is to explore the implementation of automation technology in Sarawak, Malaysia with respect to high technology manufacturer. Specifically, the objectives of this study to determine the reasons and impacts of using automation technology, to explore the development phases that are involved in the implementation of automation technology and determine the advantages and disadvantages of using automation technology in the selected high technology manufacturer in Sarawak, Malaysia. Others objective is to constructs this project is to make it as used for references for new generation and can be a sourcebook. Included in this thesis or project, there are few recommendations for those who interested to pursuing this project to more advanced level or using this as a source of reference in order to understand automation manufacturing system especially the impact of using automation technology in high technology manufacturing company especially in our country.